Alleviation of the effect of salinity on growth and yield of strawberry by foliar spray of selenium-nanoparticles. (October 2019) - Zahedi, Seyed Morteza; Abdelrahman, Mostafa; Hosseini, Marjan Sadat; Hoveizeh, Narjes Fahadi; Tran, Lam-Son Phan
Abstract: The present study investigated the beneficial role of selenium-nanoparticles (Se-NPs) in mitigating the adverse effects of soil-salinity on growth and yield of strawberry ( Fragaria  ×  ananassa Duch.) plants by maneuvering physiological and biochemical mechanisms. The foliar spray of Se-NPs (10 and 20 mg L −1 ) improved the growth and yield parameters of strawberry plants grown on non-saline and different saline soils (0, 25, 50 and 75 mM NaCl), which was attributed to their ability to protect photosynthetic pigments. Se-NPs-treated strawberry plants exhibited higher levels of key osmolytes, including total soluble carbohydrates and free proline, compared with untreated plants under saline conditions. Foliar application of Se-NPs improved salinity tolerance in strawberry by reducing stress-induced lipid peroxidation and H2 O2 content through enhancing activities of antioxidant enzymes like superoxide dismutase and peroxidase. Additionally, Se-NPs-treated strawberry plants showed accumulation of indole-3-acetic acid and abscisic acid, the vital stress signaling molecules, which are involved in regulating different morphological, physiological and molecular responses of plants to salinity. Moreover, the enhanced levels of organic acids (e.g., malic, citric and succinic acids) and sugars (e.g., glucose, fructose and sucrose) in the fruits of Se-NPs-treated strawberry plants under saline conditions indicated the positive impacts of Se-NPs on the improvement of fruit quality and nutritional values. Our results collectively demonstrate the definite roles of Se-NPs in management of soil salinity-induced adverse effects on not only strawberry plants but also other crops. Graphical abstract: Image 1 Highlights: Effect of selenium nanoparticles (Se-NPs) on salinity mitigation was studied in strawberry. Se-NPs protected photosynthetic pigments and increased key osmolytes and hormones. Se-NPs activated antioxidant system to maintain proper ROS homeostasis. Se-NPs enhanced the levels of organic acids and sugars in the fruits. Se-NPs is a solution for salinity management and improvement of fruit quality. Abstract : This study showed that selenium-nanoparticles (Se-NPs) can protect strawberry plants from the adverse effect of soil salinity by enhancing photosynthetic capacity, activating the antioxidant system, and accumulating phytohormone (e.g., IAA and ABA), proline and total soluble carbohydrate levels in stressed plants. The Se-NP approach could be recommended to the farmers for salt stress management of strawberry, as well as other crop plants grown in arid and semiarid regions that are facing with saline problems.